Bacteriophage therapy to reduce Salmonella colonization of broiler chickens - Atterbury, Robert J.; Van Bergen, M.A.P.; Ortiz, F.; Lovell, M.A.; Harris, J.A.; De Boer, A.; Wagenaar, J.A.; Allen, V.M.; Barrow, P.A. (American Society for Microbiology., 2007)
Acute enteric infections caused by salmonellas remain a major public health burden worldwide. Poultry, particularly chickens, are known to be the main reservoir for this zoonotic pathogen. Although some progress has been made in reducing Salmonella colonization of broiler chickens by using biosecurity and antimicrobials, it still remains a considerable problem. The use of host-specific bacteriophages as a biocontrol is one possible intervention by which Salmonella colonization could be reduced. A total of 232 Salmonella bacteriophages were isolated from poultry farms, abattoirs, and wastewater in 2004 and 2005. Three phages exhibiting the broadest host ranges against Salmonella enterica serotypes Enteritidis, Hadar, and Typhimurium were characterized further by determining their morphology and lytic activity in vitro. These phages were then administered in antacid suspension to birds experimentally colonized with specific Salmonella host strains. The first phage reduced S. enterica serotype Enteritidis cecal colonization by ≥4.2 log10 CFU within 24 h compared with controls. Administration of the second phage reduced S. enterica serotype Typhimurium by ≥2.19 log10 CFU within 24 h. The third bacteriophage was ineffective at reducing S. enterica serotype Hadar colonization. Bacteriophage resistance occurred at a frequency commensurate with the titer of phage being administered, with larger phage titers resulting in a greater proportion of resistant salmonellas. The selection of appropriate bacteriophages and optimization of both the timing and method of phage delivery are key factors in the successful phage-mediated control of salmonellas in broiler chickens.